The role of interleukin-17 in inflammation-related cancers - Zhang, Xingru; Li, Bangjie; Lan, Tian; Chiari, Conner; Ye, Xiaoyang; Wang, Kepeng; Chen, Ju (Frontiers in Immunology, 2025)
Emerging evidence indicates a correlation between inflammation and the development and progression of cancer. Among the various inflammatory signals, interleukin-17 (IL-17) family cytokines serve as a critical link between inflammation and cancer. IL-17 is a highly versatile pro-inflammatory cytokine that plays a pivotal role in host defense, tissue repair, the pathogenesis of inflammatory diseases, and cancer progression. During the early stages of tumorigenesis, IL-17 signaling directly promotes the proliferation of tumor cells. Conversely, IL-17 has been shown to exhibit antitumor immunity in several models of grafted subcutaneous tumors. Additionally, dynamic changes in the microbiome can influence the secretion of IL-17, thereby affecting tumor development. The specific role of IL-17 is contingent upon its functional classification, spatiotemporal characteristics, and the stage of tumor development. In this review, we introduce the fundamental biology of IL-17 and the expression profile of its receptors in cancer, while also reviewing and discussing recent advancements regarding the pleiotropic effects and mechanisms of IL-17 in inflammation-related cancers. Furthermore, we supplement our discussion with insights into the mechanisms by which IL-17 impacts cancer progression through interactions with the microbiota, and we explore the implications of IL-17 in cancer therapy. This comprehensive analysis aims to enhance our understanding of IL-17 and its potential role in cancer treatment.